2007
DOI: 10.1007/s00421-006-0385-4
|View full text |Cite
|
Sign up to set email alerts
|

Relations between psychometric profiles and cardiovascular autonomic regulation in physical education students

Abstract: This study was designed to investigate physical education (PE) students the link between mood disturbances, caused by psychological or physical stressors associated with studying, and the autonomic nervous system modifications. PE students completed the profile of mood state (POMS) questionnaire at the end of the university year. Heart rate variability (HRV) was then measured during a head-up tilt test (HUT) in those with the highest and lowest total mood disturbance (TMD) scores on three successive POMS. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Nuissier et al 36 reported a five times higher anger score and an eight times higher depression score in physical education students with the highest negative mood scores than their colleagues with the lowest negative mood scores. Therefore, although statistically significant, the differences in mood scores between our PD and control athletes were not as dramatic as seen in other studies.…”
Section: Discussionmentioning
confidence: 95%
“…Nuissier et al 36 reported a five times higher anger score and an eight times higher depression score in physical education students with the highest negative mood scores than their colleagues with the lowest negative mood scores. Therefore, although statistically significant, the differences in mood scores between our PD and control athletes were not as dramatic as seen in other studies.…”
Section: Discussionmentioning
confidence: 95%
“…This was shown firstly by the significantly higher DFAα1 at D1 in NON only (Figure 5 ), which has been associated to vagal tone decrease (Penttilä et al, 2003 ), and secondly by the difference in values of RMSSD and log HF for NON vs. FIN between PRE and D1 (see results section). Taking into account that in athletic subjects, stress has been associated to lower HRV and depressed parasympathetic drive (Nuissier et al, 2007 ; Cervantes Blásquez et al, 2009 ), this suggests that successful participants were able to efficiently relax and therefore fall asleep. The stronger decrease of vagal tone in NON, indeed, may indicate that these participants, ultimately unable to complete the race, were characterized by an impaired ability to cope with the in-race demands, already at early points of the competition, which may be reflected by lower quality of recovery (i.e., sleep quality impairment), whereas FIN displayed higher recovery potential.…”
Section: Discussionmentioning
confidence: 99%
“…Increased performance and greater parasympathetic drive in cardiac autonomic regulation are associated with increased psychological wellbeing (Cervantes Blásquez et al, 2009 ; Bisschoff et al, 2016 ). Conversely, fatigued states and increased mood disturbance have been related to decreased indexes of total HRV, as well as parasympathetic tone (Nuissier et al, 2007 ; Leti and Bricout, 2013 ; Schmitt et al, 2013 ; Flatt et al, 2017a ). In this context, impaired resting conditions present another vital influence on cardiac autonomic regulation.…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese version of the STAI has been confirmed to have adequate validity and reliability (Shimizu and Imaei 1981). These two psychological tests were used in this study, since a relationship between these scores and the cardiac autonomic nervous system in a person with no disabilities has been reported (Uyarel et al 2006;Nuissier et al 2007). Repeated examination by the POMS at weekly intervals is possible (Yokoyama and Araki 1994).…”
Section: Psychological Testsmentioning
confidence: 99%